Arab Countries in Transition : Economic Outlook and Key Challenges. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
In an environment of heightened socio-economic tensions, regional insecurity, and strained public finances, the Arab Countries in Transition (ACTs) 1 face the difficult task of delivering on the expectations for jobs and growth. Despite patchy improvements in some countries, economic growth remains subdued, private investment is weak, and external and fiscal buffers are running low. Fostering social cohesion and avoiding a downward spiral of economic and political malaise calls for urgent implementation of economic reforms and coordinated support from the international community.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet